The Effectiveness of Online Learning and Its Influence on Student Participation - Marhaeni Dwi Satyarini; Kasidi Kasidi; Sri Setyaningsih (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2022)
Online learning has been implemented for more than two semesters, amid the problems of 'stuttering' technology, lecturers and students complained about the declining quality of learning and student participation. The purpose of this study was to determine the effectiveness of the implementation of online learning in the Economic Education study program at Ivet University and its effect on student learning participation. The research sample is 50 students. They were collecting data using questionnaires and interviews. The data were analyzed using an eclectic approach, combining regression and qualitative techniques. The results showed: 1). The effectiveness of the implementation of online learning with an average score of 3.81 in the high category 2). Student participation in online learning with a mean score of 4.0 in the high category and 3). Testing the hypothesis with regression techniques obtained the regression equation Y = 38.370 + 0.309.b + e, coefficient F = 4.730 with a significance of 0.035 0.05 and R Squares = 0.090. Conclusion: online learning affects the learning participation of students in the Economic Education study program at Ivet University.